2008
DOI: 10.1021/bi800282d
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine pKa Depression by a Protonated Glutamic Acid in Human DJ-1

Abstract: Human DJ-1, a disease-associated protein that protects cells from oxidative stress, contains an oxidation-sensitive cysteine (C106) that is essential for its cytoprotective activity. The origin of C106 reactivity is obscure, due in part to the absence of an experimentally determined pK a value for this residue. We have used atomic-resolution X-ray crystallography and UV spectroscopy to show that C106 has a depressed pK a of 5.4 ( 0.1 and that the C106 thiolate accepts a hydrogen bond from a protonated glutamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
142
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(153 citation statements)
references
References 64 publications
10
142
1
Order By: Relevance
“…Among the three human cysteines, most previous studies identified Cys-106 as the most reactive and functionally important residue (15,17,26,28,50), except for one study, which identified Cys-53 to account for the redox-dependent chaperone activity and cytoprotection of DJ-1 (22 [C106EE]DJ-1 also had ASK1 binding and cytoprotective activity, albeit with lower efficacy most likely due to reduced protein stability because of the introduction of more bulky and charged residues in the sensible active site of DJ-1. Thus, higher order oxidation events at Cys-106 activate the cytoprotective protein DJ-1, and the C106DD mutation best mimics DJ-1 activation steps toward initial, non-covalent ASK1 binding.…”
Section: Discussionmentioning
confidence: 99%
“…Among the three human cysteines, most previous studies identified Cys-106 as the most reactive and functionally important residue (15,17,26,28,50), except for one study, which identified Cys-53 to account for the redox-dependent chaperone activity and cytoprotection of DJ-1 (22 [C106EE]DJ-1 also had ASK1 binding and cytoprotective activity, albeit with lower efficacy most likely due to reduced protein stability because of the introduction of more bulky and charged residues in the sensible active site of DJ-1. Thus, higher order oxidation events at Cys-106 activate the cytoprotective protein DJ-1, and the C106DD mutation best mimics DJ-1 activation steps toward initial, non-covalent ASK1 binding.…”
Section: Discussionmentioning
confidence: 99%
“…It requires the thiol-containing molecule to contain a chromophore that is sensitive only to the thiol's ionization. 24,31 This imposes a significant constraint on the general application of this method. Indeed, it has been recently demonstrated that the pKa values of 1,4-benzenedithiol (1,4-BDT) determined with the UV-vis method are highly erroneous.…”
Section: Drawbacks Of Existing Methods For Thiol Pk a Determinationmentioning
confidence: 99%
“…Several studies have shown that of the three cysteine residues in human DJ-1, Cys 106 is the most prone to oxidative modification (8,16,17). In addition, Cys 106 has a low pK a value of 5.4 and therefore exists almost exclusively as the highly reactive cysteine thiolate anion at physiological pH (18 …”
mentioning
confidence: 99%
“…Several studies have shown that of the three cysteine residues in human DJ-1, Cys 106 is the most prone to oxidative modification (8,16,17). In addition, Cys 106 has a low pK a value of 5.4 and therefore exists almost exclusively as the highly reactive cysteine thiolate anion at physiological pH (18). Replacement of Cys 106 with other amino acids in DJ-1 results in a loss of protective activity against oxidative stressors in a number of systems (15,19,20).…”
mentioning
confidence: 99%
See 1 more Smart Citation